KEPUASAN KELUARGA PASIEN SEBELUM DAN SESUDAH PERUBAHAN STATUS PENGELOLAAN DI POLI PSIKIATRI RUMAH SAKIT JIWA PROVINSI NUSA TENGGARA BARAT - Abdullah Abdullah (Master of Management, Mataram University, 2016)
ABSTRACT Patient satisfaction in hospital services is an indicator for the service quality. Mental Hospital of Nusa Tenggara Barat (RSJ NTB) as the only one technical institute in West Nusa Tenggara, specifically cover of services and development of services in mental health field has responsibility to support the realization of vision and mission of local governments to carry out the basic tasks and function as well as possible, including the success of the implementation of the national health insurance. The purpose of this research is to compare and analyze patient satisfaction before and after the status of management application become PPK-BLU in psychiatry ward in Mental Hospital of West Nusa Tenggara. The analysis used in this reserach is comparative descriptive with cross sectional approach. The research conducted in treatment room of Psychiatry ward in Mental Hospital NTB. The total number of respondents was 158 respondent. Patient satisfaction level was calculated using Parasuraman model (Responsibility, Assurance, Tangible, Empathy, and Responsiveness)), whereas the hypotheses with different two mean test for observation satisfaction before and after the local public service. Recommendations of this research is as an input and evaluation of the quality of health service in Mutiara Sukma Mental Hospital West Nusa Tenggara province. Expected later there are beterment of comfortable and improving service quality of each units that the goals to patient satisfaction continuously. Keyword: Patient satisfication, BLUD